STUDY ABOUT THE INFLUENCE OF THE PROCESS PARAMETERS OF VIBRO IMPACT CUTTING OF OPTICAL SLUGS ON THE PRODUCTIVITY OF THE PROCESS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the article, experimental studies were carried out, contributing to determination of degree of influence of the parameters of the modes of vibro-impact cutting of optical slugs on the productivity of the process. The optimal frequencies of the forced oscillations of the technological system "slug-cut disc" were reported, in which the durability of the tool and the quality of the obtained surfaces are maximum.